Postcardiotomy Veno-Arterial Extracorporeal Membrane Oxygenation: Does the Cannulation Technique Influence the Outcome? - Kalampokas, Nikolaos; Sipahi, Nihat Firat; Aubin, Hug; Akhyari, Payam; Petrov, Georgi; Albert, Alexander; Westenfeld, Ralf; Lichtenberg, Artur; Saeed, Diyar (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) may be cannulated using either central (cannulation of aorta) or peripheral (cannulation of femoral or axillary artery) access. The ideal cannulation approach for postcardiotomy cardiogenic shock (PCS) is still unknown. The aim of this study is to compare the outcome of patients with PCS who were supported with central vs. peripheral cannulation. Methods: This is a single-center retrospective data analysis including all VA-ECMO implantations for PCS from January 2011 to December 2017. The central and peripheral approaches were compared in terms of patient characteristics, intensive care unit (ICU) stay, hospitalization length, adverse event rates, and overall survival. Results: Eighty-six patients met the inclusion criteria. Twenty-eight patients (33%) were cannulated using the central approach, and 58 patients (67%) were cannulated using the peripheral approach. Forty-three patients (50%) received VA-ECMO in the operating room and 43 patients (50%) received VA-ECMO in the ICU. Central VA-ECMO group had higher EuroSCORE II (p = 0.007), longer cross-clamp time (p = 0.054), higher rate of open chest after the procedure (p < 0.001), and higher mortality rate (p = 0.02). After propensity score matching, 20 patients in each group were reanalyzed. In the matched groups, no statistically significant differences were observed in the baseline characteristics between the two groups except for a higher rate of open chests in the central ECMO group (p = 0.02). However, no significant differences were observed in the outcome and complications between the groups. Conclusions: This study showed that in postcardiotomy patients requiring VA-ECMO support, similar complication rates and outcome were observed regardless of the cannulation strategy.